Efektivitas Permainan Tradisional Dalam Pembelajaran Pendidikan Jasmani di Sekolah Dasar - Noven Christoper Butarbutar; Amir Mahmud Hasibuan; Nadia Dwi Utami; Siti Annisa; Fajar Siddik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the effectiveness of traditional games as a method of physical education learning in elementary schools. Traditional games, such as engklek, gobak sodor, bentengan, and petak umpet, not only serve as entertainment but also contribute to enhancing students' motor, social, and emotional skills. The research method used is a literature study, with thematic analysis to identify patterns and concepts from various related sources. The results show that traditional games can increase student active participation, create an inclusive and enjoyable learning atmosphere, and preserve local cultural values. Therefore, it is highly recommended that traditional games be included in the physical education curriculum to promote the overall growth of children.